Software Development From A to Z A Deep Dive into all the Roles Involved in the Creation of Software - Filipova, Olga (Apress, 2018)
Understand the big picture of the software development process. We use software every day - operating systems, applications, document editing programs, home banking - but have you ever wondered how software is created? This book guides you through the entire process, from conception to the finished product with the aid of user-centric design theory and tools. Software Development: From A to Z provides an overview of backend development - from databases to communication protocols including practical programming skills in Java and of frontend development - from HTML and CSS to npm registry and Vue.js framework. You'll also review quality assurance engineering, including the theory about different kind of tests and practicing end-to-end testing using Selenium. Dive into the devops world where authors discuss continuous integration and continuous delivery processes along with each topic's associated technologies. You'll then explore insightful product and project management coverage where authors talk about agile, scrum and other processes from their own experience. The topics that are covered do not require a deep knowledge of technology in general; anyone possessing basic computer and programming knowledge will be able to complete all the tasks and fully understand the concepts this book aims at delivering. You'll wear the hat of a project manager, product owner, designer, backend, frontend, QA and devops engineer, and find your favorite role. .